Projeto saúde, bombeiros e sociedade (PSBS) e a proposta do envelhecimento ativo: com a palavra, as mulheres - Barroso Junior, Airton Rodrigues (2024)
The project known as PSBS (Projeto Saúde, Bombeiros e Sociedade) is a public policy that aims to offer physical-occupational activities that promote the well-being of elderly people who attend its centers, while at the same time raising awareness among this population about different aspects linked to aging and other essential issues. This work evaluated the PSBS based on its origin, development and performance; investigated the understanding of participants from two of its centers located in the Maraponga neighborhood about quality of life and their aging process; found out how they feel after joining the PSBS; and also analyzed the perception of the General Commander of the Ceará Military Fire Departament (CBMCE) regarding the objectives of this public policy and the way in which it has been evaluated. Bibliographic, documentary and field research was carried out, in addition to semi-structured interviews directed to 8 members and the General Commander of the CBMCE, a reference in the leadership of the PSBS. The PSBS proved to be a unique opportunity to practice leisure, but also autonomy, which contributes to a greater feeling of control, confidence, and quality of life. There is room for the creation of private sector partnerships with the CBMCE, which can provide its audience with opportunities to deepen their knowledge, physical health and social connections. These, in turn, proved to be a very strong aspect of this policy, as they were shown to have an influence on processes of recovery from grief, depression and improvement of subjective well-being in general. Among other discoveries, it was noticed that interrupting physical activities, whether by one's own decision or by external forces, causes a feeling of tiredness and discouragement. We conclude with the idea that the PSBS, its preservation and growth are not only healthy, but essential to maintain the quality of life achieved by a large portion of the elderly in the capital and country, so that investment in this public policy needs to continue and the ways of evaluating it must be improved.